ERECTILE DYSFUNCTION IN HAEMODIALYSIS PATIENTS - Mumtaz, Asim; Anees, Muhammad; Barki, Muhammad Haris; Sami, Waqas; Hussain, Shabir; Nazir, Muhammad (Journal of Ayub Medical College Abbottabad, 2009)
Background and Objective: There is a very high prevalence of Erectile Dysfunction (ED) in dialysis patients. There is no as such available data on ED and factors affecting it in our patients. Methods: Analytical, cross-sectional, hospital based study conducted from January to March 2008, Haemodialysis unit of Shalimar and Mayo Hospital, Lahore. All male patients of end stage renal disease (ESRD) on maintenance haemodialysis therapy, whose spouses are alive and able to perform intercourse, were included in the study. Patient with cognitive and communication deficits were excluded from study. International index of erectile function-5 (IIEF-5), adopted in Urdu was used for the determination of prevalence of erectile function. Categorization of erectile dysfunction was done as mild, moderate and severe. Demographic data were collected and certain laboratory parameters (haemoglobin, haematocrit, urea, HBsAg and Anti HCV) were sent. Results: Total numbers of patient were fifty. Major cause of ESRD was diabetes mellitus 28 (56%). Most of the patients 33 (66%) have passed 10th grade or they were under 10th grade. Prevalence of ED was 86% with mean IIEF-5 score of 10.36±7.13. Majority of patients 33 (64.7%) were suffering from severe degree of ED. Factors responsible for ED are diabetes mellitus, age more than 50 year, high pre dialysis urea and Anti HCV positive patients. In this study, smoking, duration of dialysis and monthly spending is not related with ED. Conclusion: Majority of the patients suffering from ESRD, on maintenance haemodialysis are having ED. None of the patients suffering from ED were taking any treatment for it. Haemodialysis does not improve sexual dysfunction. Major factors responsible for ED are diabetes mellitus, age more than 50 years, high pre dialysis urea and Anti HCV positive patients. Keywords: Haemodialysis, erectile dysfunction, diabetes mellitus, age, IIEF-5